Optimizing Solar Panel Efficiency with Machine Learning-Powered Cleaning Robots - Akror Kavchat; Uddhav Sategay; Rushikesh Walke; Komal More; Dr. Bhausaheb E. Shinde (International Journal of Optical Innovations & Research, 2024)
Because of advancements in technology, scientists are focusing more on robots to make human existence better. IEEE Standard 1621, IEEE Standard for User Interface Elements in Power Control of Electronic Devices Employed in Office/Consumer Environments, is being used in this work to create a solar floor cleaning robot prototype through design and development. The subject robot can function in both autonomous and manual modes, in addition to other features including scheduling for a specific amount of time and a bagless dirt container with an automatic dirt disposal mechanism. The human lifestyle could be greatly improved by this work. Modern homes are becoming more intelligent and automated. People have more spare time and a more convenient existence thanks to home automation. Even though the market is still young and developing, domestic robots are becoming more common in homes and in people's daily lives. However, a surge is expected, and domestic robot usage is evolving.
Keywords: Automated Cleaners; Bluetooth; Floor cleaners; Motors; Raspberry Pi; Robotic; ultrasonic sensors